Karakteristik Sistematika Bahan Ajar Pembelajaran Baca Al-Qur'an Metode Qiraati - Hilda Fairuzia Khaidaroh Hilda; Nurul Faizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Teaching materials are one of the substantial learning elements in achieving learning objectives. This study aims to determine the characteristics contained in teaching materials for learning to read the Qur'an using the Qiraati method. The method used in this study is a qualitative research method. The data in this study include literature or textual data. Judging from the source of the data, the method of data collection is documentary. This study uses a content analysis method, which is a research method used to draw conclusions that can be corrected according to facts by emphasizing a practical-oriented context from conclusions and explanations about actual symptoms and prediction goals. The results showed that there were different characteristics in each volume. First volume 1: eliminating vague readings by getting used to reading open Harakat Fathah, second volume 2: eliminating reckless or oblique readings (short and unclear) by reading Harakat dhummah, kasroh, fathahtain, kasrohtain, dhummahtain and practicing children carefully read long and short with longer lengths, third volume 3: eliminating prolonged or dragging readings by means of reading breadfruit is pressed not extended nor is tawallud and does not lengthen mad thobi'i and the emphasis should not be broken, fourth volume 4: eliminates readings The Qur'an which is fast but not tartil or Tajwid begins by reading nun sukun with a long hum longer than one alif, fifth volume 5: straightening out the mission of volume IV and qolqolah and eliminating the reading of the Qur'an that is not Tajwid and continuing the mission volume IV, sixth volume 6: eliminating the non-Tajwid reading of the Qur'an and continuing the mission of volumes IV and V.